Financial development and employment: New panel evidence. (1st February 2021) - Ayadi, Rym; Ben Naceur, Sami; Goaied, Mohamed
Abstract: This paper adds to the recent literature on finance and employment creation by exploring the effect of finance on the labour market, using data on 143 countries from 1995 to 2015. We also examine whether the impact of financial development on labour is significantly different before and after the 2008 global financial crisis. This paper has five main findings. First, the analysis confirms the positive relationship between financial institution efficiency and access, as well as the employment rate in the linear specification. Second, the marginal returns to employment from further financial institution inclusion diminish at high levels of inclusion and turn negative when an inclusion point is reached. Third, the effects of financial market access on employment show a "U‐Shaped" relationship. Fourth, the positive effect of financial development on employment strengthens with the country's institutional quality. And fifth, there is strong support for a negative impact of financial development on employment during the global financial crisis of 2007–2008.